Physical Architecture Simulation Based on System Dynamics Modelling for an Autonomous Transportation System Scenario - Chen Liang; Zhenwu Chen; Liang Yang; Zihan Guo; Xianglong Feng; Zhijun Huang; Xiang Liu; Yuqing Qian; Yanqing Xu; Xiaochun Zhang; Ji Zhang (Journal of Advanced Transportation)
With the rapid growth of traffic demand and the development of intelligent technology, autonomous transportation system (ATS) has been considered as future transportation system. The evaluation of a designed physical architecture of ATS is necessary for understanding whether and how ATS operates and evolves automatically without manual works, and architecture simulation is a method for solving such research problem. Therefore, in this study, architecture simulation based on system dynamics modelling has been employed for physical architecture research. Under this methodology, a simulation case for scenario “Autonomous Vehicle on a Crossing in an Autonomous Transportation System” has been studied for understanding the information flow in ATS to evaluate and optimise its physical architecture of ATS. In conclusion, the system dynamic model could help researchers understand and evaluate the physical architecture’s operation of ATS by scenario analysis.